Kilka uwag leksykograficznych (na marginesie Słownika gwar zachodniopoleskich Hryhorija Arkuszyna) - Czyżewski, Feliks (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The goal of the article is to seek to answer the question how to describe folk lexis on the Slavic borderlands. On the basis of the analysis of different types of Polish, Ukrainian and Belarusian dictionaries, the author draws a conclusion that differential dictionaries that contain lexis from dialect areas of different dialectal classification do not show objective linguistic reality. He suggests that the description of lexis made according to the criterion of the opposition between dialect and literary language should be replaced by the opposition between a dialect and other dialects within one national language.